Pelatihan Pencegahan Bullying Bagi Organisasi Kemahasiswaan di Universitas Muhammadiyah Mataram - Abdul Sakban; Maemunah Maemunah; Hafsah Hafsah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The service activities that have been carried out aim to provide an understanding of bullying prevention for student organizations at the Muhammadiyah University of Mataram. The implementation method used is in the form of socialization and Focus Group Discussion (FGD). The socialization method is carried out online related to the delivery of material about preventing bullying among students and the Focus Group Discussion (FGD) method is carried out online by providing education to students regarding forms of bullying and its prevention. Based on the results of the service activities that have been carried out, it can be seen that the level of student understanding of bullying prevention is high. Thus, it can be concluded that bullying prevention training activities can provide a high level of understanding among students.